2019
DOI: 10.26873/svr-752-2019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bedding Materials on Duck’s Welfare and Growth Performance

Abstract: Ducks spend their entire life in contact with the litter material, thus the management strategies should focus on what is the best for ducks welfare and growth performance. Herein, the main object of the present study was assessing the effects of different litter materials on the ducks' welfare and growth performance. Four groups of ducks (24 duckling for each) were kept on four types of bedding materials, sawdust, plastic slatted floor, sand and without. The present study revealed several changes in duck's be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Based on the higher nal BW, ADG and lower FCR of waterfowls in NRS, studies on Yangzhou geese and Chaohu ducks reported waterfowls in NRS exhibited better growth performance than in FRS [9,24]. Similarly, in Moulard ducks, though FCR was not signi cantly affected, the higher nal BW and ADG in NRS in comparison to sawdust-FRS and sand-FRS also revealed that NRS resulted in a better growth performance [25]. However, with a lower ADG but a higher FCR of Cherry Valley ducks in NRS, Chen et al [12] reached an opposite conclusion of ducks in FRS exhibited better growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the higher nal BW, ADG and lower FCR of waterfowls in NRS, studies on Yangzhou geese and Chaohu ducks reported waterfowls in NRS exhibited better growth performance than in FRS [9,24]. Similarly, in Moulard ducks, though FCR was not signi cantly affected, the higher nal BW and ADG in NRS in comparison to sawdust-FRS and sand-FRS also revealed that NRS resulted in a better growth performance [25]. However, with a lower ADG but a higher FCR of Cherry Valley ducks in NRS, Chen et al [12] reached an opposite conclusion of ducks in FRS exhibited better growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the demonstrated impact of the living environment on productive indices [5,17] and the fact that ducks spend their entire growth period in contact with the bedding materials, we were specifically interested in determining whether different bedding materials could have varied effects on the growth performance and carcass characteristics of White Pekin ducks. Three different commercially available beddings made of coco peat, rice husks, and sawdust were evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors should be considered when determining the suitability as ideal bedding materials. This includes low moisture content (MC), high water adsorbing/holding capacity, quick drying capacity, low thermal conductivity, and acceptability as fertilizer material [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Domestic geese kept on dirt floors without litter had reduced feather cleanliness at 56 and 84 days of age compared to birds kept on perforated plastic floors (Liao et al., 2022 ). However, in Mule ducks, housing without access to bathing water on plastic slats or solid floors with one of two types of litter (sand and wood shavings), or no litter, did not influence feather cleanliness (Mohammed et al., 2019a ).…”
Section: Assessmentmentioning
confidence: 99%